Diseño e implementación de un sistema informático para la gestión de huéspedes, reservaciones y efectivo en caja en el Hotel Mongomery del Cantón "La Maná. Año 2017" - Villa Muñoz, María Elizabeth (2017)
The general objective of this research project was the implementation of a computer system for the management of guests, reservations and cash in the Mongomery Hotel in La Mana, in 2017, its implementation was motivated by the need for such establishment Service, because the registration process, selection of rooms and management of information of the guests is carried out manually, leading to delays. In order to offer an alternative solution, which allows it to improve these processes and raise the satisfaction levels of its customers. The types of research used were: bibliographical and exploratory ones that made possible the creation of a theoretical base that scientifically supports the content through the point of view of diverse authors and when dealing with a new subject it was possible to establish an overview of the variables of study. In relation to the methods it was used the deduction for the emission of conclusions of both the results of the surveys applied to the clients of the hotel and of the interview enhanced to the administrator. The analytical method was used during all the stages of the investigation, for the collection of information from primary sources that allowed to establish the characteristics and requirements of software. The results reflected that the most appropriate methodology for the development of the computer management system was XP (Extreme Programming) due to its agility in the development of the software and its simplicity in the installation; PHP, Java Scrip, Netbeans, the local Apache server and the My SQL database manager were also resorted to; by means of the execution of the tests of black box and white box, the existing anomalies and their subsequent corrections were determined, thus guaranteeing an optimum operation of the guest management system.